(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2024)
Abstract: This research study investigates the task complexity and students’ cognitive load in science of grade-11 science students in Kitobo National High School, Kitubo, Kitaotao, Bukidnon during the second quarter of the academic year 2024-2025. The study aims to examine 1. The level of task complexity for the students in science; 2. The level of students’ cognitive load in science; 3. The relationship between task complexity and students’ cognitive load in science. The participant of the study involves 87 science students from 3 different sections of grade-11 selected through purposive sampling. Participants answered a 42-item survey questionnaire divided into two parts focusing on the task complexity and cognitive load. The data collected were analyzed using statistical tool called SPSS. Analysis of the data shows several insights on the cause and effect of task complexity and cognitive load as well as the close direct proportionality of the variables. While complex task triggers the students to do more and improve their output better, there is still a need to improve in delivering and presentation of the task and lesson. A well-structured task that aligns with students' cognitive capabilities and reduce extraneous cognitive load can significantly enhance learning outcomes. By balancing task complexity with appropriate support, educators can foster deeper understanding and more effective learning experiences. Educators should continue refining task design to ensure it supports cognitive load management while promoting engagement. Further research is needed to explore how specific task structures impact different types of cognitive load across various learning environments. Additionally, developing targeted strategies to reduce extraneous load in digital learning contexts could provide valuable insights for improving online education.